PENGARUH ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA SCOOPY PADA MAHASISWA DI UNIVERSITAS TADULAKO - Rahmawati, Rahmawati (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
This study aims to determine the influence of attribute product on purchase decision of HondaScoopy motorcycles of students in Tadulako University. The type of study is descriptive causal.Sample consists of 96 respondents who selected by applying purposive sampling technique. Dataanalysis is multiple linear regressions. The results show that product attributes consist of brand,product quality, product features, product design, service, warranty, and price simultaneously havesignificant influence on purchasing decision of Honda Scoopy motorcycles of students in TadulakoUniversity; brand partially has significant influence on purchase decision of Honda Scoopymotorcycles of students in Tadulako University; product quality partially has significant influence onpurchase decision of Honda Scoopy motorcycles of students in Tadulako University; product featurespartially have significant influence on purchase decision of Honda Scoopy motorcycles of students inTadulako University; design partially has significant influence on purchase decision of Honda Scoopymotorcycles of students in Tadulako University; service partially has non-significant influence onpurchase decision of Honda Scoopy motorcycles of students in Tadulako University; warrantypartially has significant influence on purchase decision of Honda Scoopy motorcycles of students inTadulako University; price partially has significant influence on purchase decision of Honda Scoopymotorcycle of students in Tadulako University.